1996
DOI: 10.1007/bf01806157
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relations of s-adenosylmethionine decarboxylase inhibitors on the growth of MCF-7 breast cancer cells

Abstract: SAMDC is a key enzyme in the biosynthesis of spermidine and spermine, 2 polyamines that are essential for cell proliferation. Inhibition of polyamine biosynthesis is often targeted as a therapeutic strategy to suppress cancer cell growth as these cells contain elevated levels of polyamines. We examined the effect of a new group of SAMDC inhibitors, CGP33829, CGP35753, CGP36958, CGP39937, and CGP48664, (obtained from Ciba-Geigy, Basel, Switzerland), and their parent compound, MGBG, on the proliferation of MCF-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…If DFMO was added to the cells with spermidine, growth inhibition could be prevented [7]. Similarly, when spermine was included during the incubation of CGP 48664, growth inhibition was not seen [38]. These results indicate the specificity of DFMO and CGP 48664 in inhibiting the appropriate biosynthetic enzymes.…”
Section: Polyamines In Cell Cyclementioning
confidence: 59%
See 2 more Smart Citations
“…If DFMO was added to the cells with spermidine, growth inhibition could be prevented [7]. Similarly, when spermine was included during the incubation of CGP 48664, growth inhibition was not seen [38]. These results indicate the specificity of DFMO and CGP 48664 in inhibiting the appropriate biosynthetic enzymes.…”
Section: Polyamines In Cell Cyclementioning
confidence: 59%
“…A new generation of SAMDC inhibitors was synthesized recently, and one of these compounds, referred to as CGP 48664, appears to be particularly useful as a novel cancer therapeutic agent ( fig. 3) [37,38]. MCF-7 cells treated with 1 mM DFMO or 1 mM CGP 48664 showed comparable levels of growth inhibition [39].…”
Section: Polyamines In Cell Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…In HeLa, cells transfected with constructs containing 5‐deletion inserts from the ODC gene promoter, significantly decreased activity was observed after deletion of the −115 to −72 region of the promoter [31]. Previous studies have reported that 17β‐estradiol (E2) induces ODC gene expression in breast cancer cells and the rat uterus [43–48]. We have investigated the mechanism of hormone‐induced ODC gene expression in MCF‐7 breast cancer cells and E2‐induced luciferase (reporter gene) activity in cells transfected with pODC1 which contained a −164 to +29 ODC gene (human) promoter insert linked to a bacterial luciferase gene.…”
Section: Introductionmentioning
confidence: 99%
“…Agents that target other polyamine metabolic enzymes (FIG. 1) are also potent inhibitors of cancer growth in experimental model systems 19,20 , and some of these agents are either under evaluation or have been evaluated in human clinical cancer therapeutic trials 21,22 .…”
mentioning
confidence: 99%